Kesejahteraan Rumah Tangga dalam Pengaruh Wanita Kepala Rumah Tangga - Agung Priyo Utomo; Rini Rahani (Faculty of Social and Political Sciences, Universitas Gadjah Mada, 2013)
This study focused on the welfare of the household headed by a working widow, viewed through the assets and the quality of their residence. Household welfare level is based on the wealth index. Ordinal logistic regression analysis show that level of education, age and employment status significantly influence the level of wealth of households headed by them. The higher the educational level of a widow, the household will tend to be richer. The older widows, the smaller tendency to have poor household. Households headed by widows who work in the agricultural sector, have a greater tendency to get a lower level of wealth status compared with who work in the non-agricultural sector.